PENINGKATAN KREATIVITAS SISWA DALAM PRAKTEK MENGGAMBAR BENTUK DENGAN MENGGUNAKAN MEDIA JOBSHEET PADA SISWA KELAS VII-A SMP N 4 LEMBANG JAYA KABUPATEN SOLOK - RADINA, Ir. Drs. Heldi, M.Si, Dra. Ernis, M.Pd (Universitas Negeri Padang, 2014)
This article aims to improve students' ability to draw shapesusing jobsheet media. This type of research is a classroom actionresearch, the research was conducted in semester from January to June2014 A class VII SMP 4 Lembang Jaya with the number 34 in thelearning material to draw shapes. This classroom action researchcarried out by 2 cycles with research steps are, (1) planning, (2)action, (3) observation, (4) reflection. Data collection tools withobservation, field notes, questionnaires and learning outcomes.From the data in the study may results: an increase in the abilityof students who look at some numbers first cycle and cycle II. For theobserved ability: the ability of the student activity increased 81.7% to88.3%, the ability of students' creativity interaction of 75% to 86.1%and 78.3% of the teacher's activities be 86.67%. Thus, learning todraw shapes with jobsheet models showed significant improvementand can be said to be successful in improving students' skills indrawing form.Keywords: Creativity students, drawing shapes, jobsheet media.